2020
DOI: 10.1002/cam4.3214
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels and risk of kidney cancer incidence and mortality: A prospective cohort study

Abstract: Worldwide there are more than 330,000 new cases of kidney cancer diagnosed each year, accounting for 2.4% of all cancers. 1 In developed regions such as Europe, North America, Australia/New Zealand, and Japan, kidney cancer is the seventh most common cancer. The incidence of kidney cancer has been increasing globally in the last 50 years. 2 In most countries, the average annual growth rate is about 2% to 3%. 3 The most common subtype of kidney

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
10
1
1
Order By: Relevance
“…Among the other kidney function biomarkers, we further discovered an underlying negative genetic causal inference of urate on kidney cancer in the sensitivity analysis, excluding instrumental SNPs related to body composition and diabetes. That was interestingly opposite to many previous observational studies 60,61 . The reason might due to the horizontal pleiotropy, which could influence the direction of causality, as the intercepts of MR–Egger were significant( p = 0.001).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Among the other kidney function biomarkers, we further discovered an underlying negative genetic causal inference of urate on kidney cancer in the sensitivity analysis, excluding instrumental SNPs related to body composition and diabetes. That was interestingly opposite to many previous observational studies 60,61 . The reason might due to the horizontal pleiotropy, which could influence the direction of causality, as the intercepts of MR–Egger were significant( p = 0.001).…”
Section: Discussioncontrasting
confidence: 86%
“…That was interestingly opposite to many previous observational studies. 60 , 61 The reason might due to the horizontal pleiotropy, which could influence the direction of causality, as the intercepts of MR–Egger were significant( p = 0.001). In addition, this might support the potentially protective role of urate in cancers as an antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxanthine, xanthine, and uric acid are the last components in the catabolism of purine nucleotides adenosine and guanosine phosphate. Extensive epidemiological evidence showed that elevated baseline serum uric acid (hyperuricemia) is associated with increased cancer risk across cancer types [ 26 ], and in RCC in particular [ 27 ]. The effect seems to be exerted by the upregulation of key components of chronic inflammatory pathways such as adiponectin, C-reactive protein, and leptin [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is the end product of the purine metabolism pathway, and is an antioxidant scavenging free radicals in the body (8,9). Recent evidences have linked serum uric acid (SUA) to cancer risks in adulthood (10,11). Studies show that hyperuricemia is associated with an increased cancer incidence and mortality (12), while some other conflicting reports have suggested a protective role of SUA in cancer due to its antioxidant properties (13,14).…”
Section: Introductionmentioning
confidence: 99%